(untitled) (Research, Society and Development, 2020)
The aim of this study is to share interdisciplinary reflections on collective health conducted in the Collective Health discipline at the undergraduate level of a higher education institution in Rio Grande do Sul. This is a descriptive, exploratory and qualitative research, with forty and five students from the Collective Health discipline as participants. Data collection occurred through the performance of a concept map activity, being analyzed with approximations of Bardin’s Content Analysis (2016). It was found that students understand the importance of collective health in their training contexts, inferring about important aspects identified in mental maps. The articulations between collective health and secondary themes stimulated the construction of effective and constructive problematizations about the theme with emphasis on interdisciplinary practices. Thus, the study enabled the exchange of information and comprehensive reflection on public health and the interdisciplinary performance of students.